2010
DOI: 10.1152/jn.00017.2010
|View full text |Cite
|
Sign up to set email alerts
|

Release and Elementary Mechanisms of Nitric Oxide in Hair Cells

Abstract: The enzyme nitric oxide (NO) synthase, that produces the signaling molecule NO, has been identified in several cell types in the inner ear. However, it is unclear whether a measurable quantity of NO is released in the inner ear to confer specific functions. Indeed, the functional significance of NO and the elementary cellular mechanism thereof are most uncertain. Here, we demonstrate that the sensory epithelia of the frog saccule release NO and explore its release mechanisms by using self-referencing NO-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…NOS subtypes have been immune-labeled in vestibular and cochlear epithelia (Lysakowski and Singer, 2000) and specifically eNOS has been labeled in the type I hair cell calyx (Hess et al, 1998a; Hess et al, 1998b). Lv et al, (2010) using NO-selective electrodes measured a 3 fold release of NO in frog saccule neuroepithelium following application of ACh. In earlier studies, Chen and Eatock (2000) found that application of 4 NO donors inhibited the current I K,L in type I hair cells and patches of their membranes from 33 to 76%.…”
Section: Discussionmentioning
confidence: 99%
“…NOS subtypes have been immune-labeled in vestibular and cochlear epithelia (Lysakowski and Singer, 2000) and specifically eNOS has been labeled in the type I hair cell calyx (Hess et al, 1998a; Hess et al, 1998b). Lv et al, (2010) using NO-selective electrodes measured a 3 fold release of NO in frog saccule neuroepithelium following application of ACh. In earlier studies, Chen and Eatock (2000) found that application of 4 NO donors inhibited the current I K,L in type I hair cells and patches of their membranes from 33 to 76%.…”
Section: Discussionmentioning
confidence: 99%
“…In type I hair cells from rat semicircular canals, the addition of NO donors to the external solution reduced the instantaneous currents evoked by voltage steps from À67 mV, which were principally carried by I K,L channels [21]. In hair cells from frog saccules, Ca 2+ -activated K + currents were reversibly enhanced after application of NO by increasing the open probability of BK channels [22]. In posterior pituitary nerve terminals, NO enhanced Ca 2+ -activated K + channel activity by activating guanylate cyclase (GC) and cyclic guanosine monophosphate (cGMP)-dependent protein kinase (PKG) [23].…”
Section: Discussionmentioning
confidence: 96%
“…In the hair cells of frog saccules, NO reduces whole-cell Ca 2+ currents and drastically decreases the open probability of single-channel events of the L-type and non-L-type Ca 2+ channels [22]. The Ca 2+ channel modulation by NO also implies the participation of the NO-cGMP-PKG system [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations